Impact of statin type and intensity on cisplatin-related hearing loss. Issue 28 (1st October 2022) - McCullough, Emilee; Shreenivas, Aditya V.; Spitzer, Stephanie; Schroeder, Michelle; Szabo, Aniko; Friedland, David; Wong, Stuart J.
Abstract : 192 Background: Ototoxicity is a common and treatment-limiting side effect of cisplatin. Rates of permanent hearing loss due to cisplatin treatment range from 40 to 80% and are associated with considerable morbidity and negative impact on quality of life. Currently, there are no FDA-approved therapies for preventing hearing loss caused by cisplatin. HMG-CoA reductase inhibitors (statins) are of interest due to putative pleiotropic effects, decreasing inflammation and oxidative stress. Some preclinical and retrospective studies have shown reduction in cisplatin-related hearing loss with concurrent administration of statins. Objectives: This study's primary objective was to evaluate the impact of statin use on cisplatin-related hearing loss rates measured by change in Chang Grade (CG). Chang criteria was chosen as it allows for evaluation of hearing loss severity without the need for word recognition. This study also assessed the effect of statin dose intensity, cisplatin dose, and concurrent use of ototoxins on cisplatin-induced hearing loss. Methods: We performed a retrospective chart review of adult patients who received cisplatin within a single health care network between March 2010 and December 2020. Patients were included in this IRB-approved analysis if they had baseline and follow-up audiograms prior to and after cisplatin treatment. Each patient had data collected on primary cancer location, cumulative cisplatin dose, chemotherapy regimen, concurrent radiation treatment to the head and neck area, and ototoxin use. In addition, data on the type of statin used, its dose intensity were collected when applicable. Multivariable analysis of change in CG (primary outcome) was performed using logistic regression with generalized estimating equations. Results: A total of 367 patients were included in this study, of which 87 were using statins and 280 were not using statins concurrently during cisplatin treatment. Median age of study population was 63 and there was a male predominance (67%). Change in CG did not differ between statin users and non-statin users (p = 0.36). In the multivariable analysis, adjusting for statin use and age, hearing loss was predicted by cisplatin dose (OR 1.19 per 100mg; 1.09-1.30; p < 0.001) and use of radiation therapy (OR = 2.04, 95% CI: 1.34-3.10, p < 0.001). Statin intensity did not have a significant effect on the change in CG when evaluating low-intensity (p = 0.34), moderate intensity (p = 0.77) or high-intensity (p = 0.44) compared to no statin use. Type of statin use and concurrent use of ototoxins also did not have a significant impact on the changes in CG. Conclusions: To our knowledge this is one of the largest retrospective analyses of statin's impact on cisplatin related hearing loss. Our study found no difference in changes in CG hearing loss between statin users vs non-statin users. As expected, total cisplatin dose (mg) and concurrent radiation treatment remain important predictors of hearing loss.